Avaliação dos fatores de risco à cárie dentária em pacientes pediátricos portadores de necessidades especiais - Vasconcelos, Rebeca Bastos (2014)
When it comes about basic or specialized dental care, children with disabilities still represent a portion of the population less favored and studied The present study aimed to describe the profile of oral health using the ICDAS criteria and evaluate the association between lesions and caries experience with the risk factors for dental caries in patients with pediatric patients with special needs. The sample was composed by children of both gender, 4-12 years with varied diagnoses, linked to extramural projects that provide dental care at the Federal University of Ceará (UFC) and the University of Fortaleza (UNIFOR). Questionnaire was used to access the general and oral health of these children and then a clinical evaluation was made by a professional well-trained and calibrated in the evaluation of criteria of caries (ICDAS). It was observed that the sample of this clinical study was composed by 110 male children (55 %) and 90 females (45 %), where the most prevalent was the age between 4-6 years (n= 66 children, 33 %) and the category with the most common diagnosis was neurology (n= 109, 54.5 %). The ICDAS criteria for caries prevalence showed that 172 (86 %) children had their tooth surfaces classified as greater than 2 ICDAS code. Statistical analysis of data was done using the Kruskal -Wallis test , Mann - Whitney, applying logistic regression analysis (p≤ 0.05). We detected some statistically significant differences between the values of ICDAS: study site (ICDAS4 - 6DPR , p= 0.02; ICDAS4 - 6SPR, p= 0.01; CDAS1-3 4 -6D, p= 0.05), dentition stage (ICDAS CI, p= 0.08; ICDAS4 - 6DPR, p = 0.004 ; ICDAS4 - 6SPR, p< 0.001), habit of checking oral hygiene (ICDAS CI, p= 0.03; ICDAS4 - 6S, p= 0.03), flossing (ICDAS CI, p= 0.006 ; ICDAS4 - 6S , p= 0.01; ICDAS1-3 4-6D, p= 0.009), diet high in sugar (ICDAS4 - 6S ,p= 0.01), food consistency (ICDAS4-6 DPR, p= 0.03) and the use of baby bottle (ICDAS CI, p= 0.02 ; ICDAS4 - 6S , p= 0.01). Logistic regression analysis identified the factors age (4-6 years X2 = 4.588, OR = 3.228, p= 0.032), brain injury (X2 = 8.995 presence, OR= 0.196 , p= 0.003) , limited range of motion (X2= 5.749 presence, OR= 3.691, p= 0.016) and bad oral habits (presence X2= 17.925, OR= 4.272 , p= < 0.001) as risk factors to dental caries. We can conclude that the sample of children with needs presented high prevalence of caries, most of them cavitated, identifying several risk factors. Risk factors for dental caries indicated in this study can guide future studies in this population, besides being essential to establish control strategies of caries during the planning or execution of dental treatment.